Tari Dedare Nyesek - Alwan Hafiz; M Ridwan Markarma; Hary Murcahyanto; Ummi Risti Ayuni Rahman; Sopiroyani Sopiroyani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
ABSTRACT This research aims to describe the existence of Dedare Nyesek dance to the appreciation of the community in art activities in the Village of East Pringgasela Lombok Timur Regency. The method used in this research is descriptive qualitative. Data collection is done by observation, interview, and documentation. The results showed that the existence of Dedare Nyesek dance in Pringgasela Village is evidenced by the use of Dedare Nyesek dance as an art learning material in schools. Besides, Dedare Nyesek dance is also often performed at major events as government support to preserve this dance. People's appreciation of Dedare Nyesek dance is still lacking. This is due to the lack of Dedare Nyesek dance performance as well as the lack of public understanding of the meaning contained in the dance. The conclusion of the research is to preserve or improve the existence of Dedare Nyesek dance can be done by making Dedare Nyesek dance as a learning material in school. Besides, the manager and the Cultural Office also strive to display in major events held by the Cultural Office of NTB. Keywords: Appreciation, Dance, Dedare Nyesek, Existence